Uwarunkowania zmian rozwojowych w wybranych modelach rodziny = Determinants of changes in select models of the family - Liberska, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article contains the original classification of the family models - relating to the principle of dichotomy. The text compares the features of two types of model of family: traditional and alternative. It focuses on the analysis of the changes of the level of balance in the family system in connection with events normative and not only (general various events in a person's life: the expected and unexpected). The article refers to the equilibration processes in family system and indicates the relationship between them and the level of psychosocial and biological health of family.
Keywords: rozwój indywidualny; modele rodziny; równoważenie w systemie; zmiany rodziny; development of an individual; model of family; equilibration in the system; changes of the family